2019
DOI: 10.1177/1687814019842034
|View full text |Cite
|
Sign up to set email alerts
|

Strength analytical solution to ultra-high-speed permanent magnet rotor considering temperature gradient and segmental permanent magnet effect

Abstract: Ultra-high-speed permanent magnet synchronous motors usually adopt the rotor in which a sleeve is interference fitted onto a ring permanent magnet or segmental permanent magnets. The rotors are always subject to the extreme working condition (e.g. high speed and high temperature). In order to predict the strength of the rotor, this article proposes analytical models considering three types of stress sources such as interference fit, centrifugal force, and temperature gradient. Examples are calculated and discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Zhang [22] studied the influence of different protective sleeves on stress distribution using an analytical method. Chen [23,24] established a rotor stress analytical model based on the plane stress problem for a high-speed surface-mounted permanent magnet synchronous motor rotor, and then analyzed the relationship between speed, protective sleeve thickness, fit amount and rotor strength.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [22] studied the influence of different protective sleeves on stress distribution using an analytical method. Chen [23,24] established a rotor stress analytical model based on the plane stress problem for a high-speed surface-mounted permanent magnet synchronous motor rotor, and then analyzed the relationship between speed, protective sleeve thickness, fit amount and rotor strength.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al [11] conducted a mechanical analysis according to the thickness of a metallic sleeve and shrink fitting, as well as an electromagnetic analysis considering eddy currents in a metallic sleeve. Cheng et al [12] proposed analytical models of a metallic sleeve considering three types of stress sources, interference fit, centrifugal force and temperature gradient. Ahn et al [13], Shang et al [14] and Xu et al [15] presented numerical analyses of metallic sleeves in different high speed applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is found that when the segmented magnets are under tensile stress, sleeve stress concentration will occur due to the magnet edging effect [16]. Meanwhile, the seam between the segmental PM should be filled with a certain material to decrease the stress concentration caused by edges of the segmental PM [20].…”
Section: Introductionmentioning
confidence: 99%